Design and analysis of security protocol for communication - Goyal, Dinesh, 1976-; Balamurigan, A.; Peng, Sheng-Lung; Verma, O. P. (Telecommunications engineer) (John Wiley & Sons, Inc. ; Scrivener Publishing LLC, 2020)
"The purpose of designing this book is to discuss and analyze security protocols available for communication. Objective is to discuss protocols across all layers of TCP/IP stack and also to discuss protocols independent to the stack. Authors will be aiming to identify the best set of security protocols for the similar applications and will also be identifying the drawbacks of existing protocols. The authors will be also suggesting new protocols if any. The purpose of designing this book is to discuss and analyze security protocols available for communication. Objective is to discuss protocols across all layers of TCP/IP stack and also to discuss protocols independent to the stack. Authors will be aiming to identify the best set of security protocols for the similar applications and will also be identifying the drawbacks of existing protocols. The authors will be also suggesting new protocols if any"--